THE ILLUSION: AN OLD–NEW FORM OF IDEOLOGY IN THE SERVICE OF GOOD OR EVIL - VASILJEVIC, BOZIDAR (Politeia, 2025)
The Illusion occupies a central place in the human quest for meaning, shaping the ways in which we perceive, interpret, and act upon the world. It is neither purely deceptive nor inherently liberating, but a dynamic interplay between construction and concealment. By creating symbolic frameworks, illusions allow us to transform uncertainty into coherence and chaos into orientation. Yet, the same force that sustains hope and collective identity can also distort reality, preserve power hierarchies, and silence alternative perspectives. Within contemporary societies — increasingly defined by media saturation, digital hyperreality, and fragmented truths — the role of illusion becomes even more complex and urgent. Understanding its double-edged nature is not a matter of rejecting illusions altogether, but of discerning when they serve life, creativity, and freedom, and when they become instruments of manipulation, control, and existential detachment.
Keywords: Illusion; good and evil; power; freedom; hyperreality; truth